Restorative Justice Dalam Tindak Pidana Terorisme Terhadap Anak Berhadapan Dengan Hukum - Ping, Manuel Farsi; Kusnadi, Sekaring Ayumeida (Universitas Gorontalo, 2025)
Terrorism crimes involving children are becoming an increasingly urgent problem around the world, as they have a serious impact on individuals and society. This study aims to analyze the legal regulation of the application of restorative justice and the application of restorative justice in terrorism crimes involving children facing the law. In this context, restorative justice is suggested to be a qualified solution in dealing with children facing the law. The restorative justice approach emphasizes redress rather than retribution, offering a more humane alternative to responding to these complex cases. This study uses normative legal research methods by analyzing relevant laws and regulations as well as related literature studies. The results of the study show that restorative justice in the context of terrorism crimes has not been explicitly regulated in the laws and regulations in Indonesia. In its application, there is a legal vacuum because there is no law that explicitly regulates restorative justice for children to face the law in terrorism crimes, because considering that terrorism crimes are crimes that have a wide impact and threaten the safety of many people. To address this legal vacuum, special regulations are needed that regulate in detail how children involved in terrorism crimes are treated, taking into account rehabilitation and deradicalization to protect and guarantee their rights and get fair and balanced treatment between ensuring justice for victims, providing appropriate protection and support for children, and protecting society.